EXPLORING PROTEIN TARGETS OF TRITERPENE SAPONINS (C₅₄H₈₆O₂₄): A BIOINFORMATICS APPROACH TO NOVEL THERAPEUTIC DEVELOPMENT - SANTOSO, SETIYO BUDI; SYARIFUDDIN, ALFIAN; WARDANI, ARIEF KUSUMA; WIDIASTUTI, VIAN PUTRI; NINDA, MAY FAHTUN (International Journal of Applied Pharmaceutics, 2025)
Objective: The exploration of triterpene saponins as novel therapeutic agents is essential due to the rising prevalence of chronic diseases and limitations of current treatments. These compounds exhibit diverse biological activities, particularly anti-inflammatory and anticancer effects; however, their systematic identification and protein target interactions remain underexplored. Methods: Triterpene saponin compounds were identified using the KNApSAcK database, prioritized via the ChEMBL database, and further analyzed using SuperPred to predict high-confidence protein interactions. A protein interaction matrix was constructed to map therapeutic targets and clinical indications. Furthermore, glycosidic linkage variations among the compounds were examined using a Structure–Activity Relationship (SAR) approach based on valence bond theory, providing a comprehensive bioinformatics-based framework for therapeutic potential assessment. Results: Seven compounds classified as triterpene saponins (C₅₄H₈₆O₂₄) were selected. Structural variations were observed in sugar moieties, side chains, functional groups, stereochemistry, and glycosidic linkages, contributing to their chemical diversity and potential specificity in protein interactions. Conclusion: Our study highlights the potential of triterpene saponins (C₅₄H₈₆O₂₄) as promising drug candidates targeting key proteins, including APEX1, TLR-4, and KinaseP110.